INCREASING OF CRITICAL THINKING STUDENTS THROUGH COOPERATIVE LEARNING MODEL TPS TYPE (THINK-PAIR-SHARE) IN SOCIAL STUDIES LEARNING (CLASSROOM ACTION RESEARCH IN CLASS VIII-1 / IBNU THUFAIL FITRAH INSANI II JUNIOR HIGH SCHOOL) - Alfian, Rian (International Journal Pedagogy of Social Studies, 2017)
Abstract-This research is motivated by the problems found in the early observation in class VIII-1 / Ibnu Thufail Islamic intergrated of Junior High School Fitrah Insani II related to the critical thinking ability of learners. Lack of courage of learners in answering and asking is a low critical thinking indicator in Social studies learning. Alternative problem solving chosen is the application of cooperative learning model TPS (Think-Pair-Share) type. The problem formulation in this research is "whether by applying the TPS learning model can improve the critical thinking ability of learners?". The research method used is Classroom Action Research with research design is model Kemmis and Mc Taggart covering several stages there are, planning, implementation, observation and reflection. Data collection techniques used were observation, interview, documentation, and field notes. The critical thinking indicator developed in the study refers to the ability to provide simple explanations, build basic skills, make inferences, make further explanations, and organize strategies and techniques. The results concluded that first, the research planning is well designed by the teacher through the development of the model in accordance with the instrument made. Second, the implementation of the action is done in three cycles by distributing worksheets and video to learners for pair discussions. Third, learners experience improvement of critical thinking ability in every cycle. Fourth, the constraints that occur are time allocation, learners' understanding of learning steps, and classroom management. These constraints are resolved by improvements in each cycle. This research shows that cooperative learning model of TPS type can improve the critical thinking ability of students in social studies learning.Keywords: Critical Thinking, Cooperative Learning, TPS (Think-Pair-Share), Social Studies Learning